Busana Pengantin Koto Gadang Bermotif Pucuak Rabuang sebagai Penguat Identitas Budaya - Latifah Anjali; Dini Yanuarmi; Mega Kencana; Fadri Rahmat (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2026)
Bridal attire is an important element in a wedding ceremony that not only functions as a body covering, but also represents cultural identity. The final project work entitled Koto Gadang Bridal Attire with Pucuak Rabuang Motif Application aims to design, realize, and display Koto Gadang bridal attire by applying the Pucuak Rabuang motif as an aesthetic and symbolic element. The motif was chosen because it symbolizes growth, hope, and the beginning of a new life that is in line with the values ​​of marriage. The process of creating the work was carried out through three stages, namely exploration, design, and realization. The exploration stage includes observation, interviews, and literature studies. The design stage includes the preparation of mood boards, sketching, design selection, and design refinement. The realization stage includes pattern making, clothing construction, and the application of embroidery and sequin embroidery techniques. The dresses were made using bridal satin, Pandai Sikek songket, and brocade tulle with dominant colors of maroon, cream, and gold. The final work consists of one ready-to-wear dress, one deluxe ready-to-wear dress, and two haute couture bridal dresses. This work is expected to contribute to innovation in Minangkabau bridal wear while preserving the cultural values ​​inherent in the Koto Gadang traditional attire.